2019
DOI: 10.1016/j.compositesb.2018.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food chemicals and temperature on mechanical reliability of bio-based glass fibers reinforced polyamide

Abstract: Effect of food chemicals and temperature on mechanical reliability of bio-based glass fibers reinforced polyamide,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The decrease in the RCF-reinforced modulus was much larger due to the aging compared to the raw material ones. A decreasing Young´s modulus because of moisture absorption due to high humidity or because of increased temperatures have also been seen in the studies by Arif et al [ 42 ] and Basso et al [ 10 ]. Both studies have shown a correlation of cracks and damages with aging and the fracture behavior, resulting in a lower Young’s modulus and tensile strength.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The decrease in the RCF-reinforced modulus was much larger due to the aging compared to the raw material ones. A decreasing Young´s modulus because of moisture absorption due to high humidity or because of increased temperatures have also been seen in the studies by Arif et al [ 42 ] and Basso et al [ 10 ]. Both studies have shown a correlation of cracks and damages with aging and the fracture behavior, resulting in a lower Young’s modulus and tensile strength.…”
Section: Resultssupporting
confidence: 55%
“…Several studies have already examined cellulose fiber-reinforced bio-based polyamides, e.g., PA4.10, PA6.10, PA10.10, and PA11. They have shown significant increases in all mechanical properties, especially that the notched impact strength increases depending on the fiber content [ 10 , 11 , 12 ]. In addition, the relationship between the fiber-matrix adhesion and the mechanical properties has also been addressed in different studies [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nylon 6,6 with 50 wt.% glass fibre reinforcement represent high tensile strengths and elastic modulus. The highest value of strength and modulus were perceived for the glass fibre composites, attributable to higher strength, stiffness, better interfacial bonding of glass fibre (Basso et al, 2019;Mortazavian and Fatemi, 2015).…”
Section: Resultsmentioning
confidence: 97%